258 Scientific correlatives from LCCC 1525: a phase II study of a priming dose of cyclophosphamide prior to pembrolizumab to treat metastatic triple negative breast cancer. (9th November 2020) - Woodcock, Mark; Anders, Carey; Swearingen, Amanda Van; Moore, Dominic; Sambade, Maria; Cuaboy, Luz; Garrett, Amy; McKinnon, Karen; Cowens, Kristen; Bortone, Dante; Calhoun, Benjamin; Carey, Lisa; et al.
Abstract : Background: In metastatic triple negative breast cancer (mTNBC), median progression-free survival (PFS) with chemotherapy alone is approximately 2–4 months 1 and improvements with single agent checkpoint inhibitors (CI) are limited by modest response rates. Murine breast cancer models have demonstrated a role for intratumoral regulatory T cells (Tregs) in modulating response to CIs. 2 A phase II clinical trial was conducted to test the hypothesis that a single, priming dose of cyclophosphamide prior to pembrolizumab would improve PFS in mTNBC. Here we present the correlative genomic and immunologic analyses from this study. Methods: This trial (https://clinicaltrials.gov/ct2/show/NCT02768701 ) recruited 40 patients with largely pretreated mTNBC. Response was defined as >30% decrease in imaging-assessed disease burden. Clinical benefit was defined as treatment response or stable disease. Tumor specimens were collected prior to enrollment, and peripheral blood mononuclear cell (PBMC) samples taken prior to cyclophosphamide and before each cycle of pembrolizumab. RNA sequencing was performed on tumor samples for gene expression and immune repertoire reconstruction. Targeted sequencing of the T-cell beta chain, IG kappa, lambda and heavy chain (TRB, IGK, IGL, and IGH, respectively) on PBMCs captured the peripheral immune repertoire. Whole exome sequencing was performed on tumor samples with PBMCs serving as a matched normal. Results: Of 40 patients enrolled, 31 patients had tumor RNA-seq and at least 15 had matched PBMC-derived immune chains capturing both pre and post treatment. When preliminary RNA-seq samples (n=22) revealed upregulation in B-cell receptor pathways and related gene signatures (figure 1), we updated our planned analysis to exclude tumor specimens collected from lymph nodes. In our final analysis, response to therapy (4 of 25, 16%) was associated in tumor RNA-Seq with gene pathways involving programmed cell death and MAPK activation, while non-responding tumors were enriched in G-protein signaling and inhibition of insulin secretion (figure 2a, b, table 1). Immune gene signatures related to NK cells and B-cell activation, signaling and interaction with T follicular helper cells, 3–7 were associated with response (figure 2g). Pre-treatment immune repertoire measures demonstrated a significant association between increased peripheral IGH abundance and richness, and both future clinical benefit and response to therapy (figure 3a-d). Conclusions: Response to CI therapy was associated with immunogenomic features of programmed cell death and B-cell activation. Pre-treatment circulating immunoglobulin diversity measures (high IGH abundance and IGH richness) also correlated with future response to therapy. Taken together, these data suggest that B-cell activity contributes significantly to response to CI therapy in mTNBC. Acknowledgements: UNC Office of Clinical and Translational Research (OCTR), High Throughput Sequencing Facility (HTSF), and UNC Bioinformatics Core. We also thank the patients in this study and their families, without whom this study would not have been possible. Trial Registration: Clinical Trials. gov: NCT02768701 . Ethics Approval: All patients provided written informed consent, and the study was approved by each institution's institutional review board (No. NCT02768701 ). References: Tutt A, Tovey H, Cheang MCU, et al. Carboplatin in BRCA1/2-mutated and triple-negative breast cancer BRCAness subgroups: the TNT Trial. Nat Med 2018;24(5):628–637. doi:10.1038/s41591-018-0009-7 Taylor NA, Vick SC, Iglesia MD, et al. Treg depletion potentiates checkpoint inhibition in claudin-low breast cancer. J Clin Invest 2017;127(9):3472–3483. doi:10.1172/JCI90499 Hollern TFH B cell: Hollern DP, Xu N, Thennavan A, et al . B Cells and T Follicular Helper cells mediate response to checkpoint inhibitors in high mutation burden mouse models of breast cancer. Cell 2019;179(5):1191–1206.e21. doi:10.1016/j.cell.2019.10.028 Iglesia B cell: Iglesia MD, Vincent BG, Parker JS, et al . Prognostic B-cell signatures using mRNA-seq in patients with subtype-specific breast and ovarian cancer. Clin Cancer Res 2014;20(14):3818–3829. doi:10.1158/1078-0432.CCR-13-3368 Fan IGG: Fan C, Prat A, Parker JS, et al . Building prognostic models for breast cancer patients using clinical variables and hundreds of gene expression signatures. BMC Med Genomics 2011;4:3. Published 2011 Jan 9. doi:10.1186/1755-8794-4-3 Bindea: Bindea G, Mlecnik B, Tosolini M, et al. Spatiotemporal dynamics of intratumoral immune cells reveal the immune landscape in human cancer. Immunity 2013;39(4):782–795. doi:10.1016/j.immuni.2013.10.003 Prat Claudin: Prat A, Parker JS, Karginova O, et al . Phenotypic and molecular characterization of the claudin-low intrinsic subtype of breast cancer. Breast Cancer Res 2010;12(5):R68. doi:10.1186/bcr2635